Associations between nutrition knowledge and obesity-related attitudes and physical activity among young adults from Kenya, South Africa, and the United Kingdom - Siphiwe N Dlamini; Asanda Mtintsilana; Witness Mapanga; Ashleigh Craig; Shane A Norris (The South African Journal of Clinical Nutrition, 2023)
Objective: This study’s aim was to test associations between nutrition knowledge and obesity-related attitudes and physical activity (PA) among 3000 18–35-year-old men and women from Kenya, South Africa (SA), and the United Kingdom (UK). Methods: A cross-sectional online survey was conducted in April 2022. To estimate nutrition knowledge, dietary recommendation knowledge score was computed using the standard General Nutrition Knowledge questionnaire. Obesity-related attitudes were from the British Social Attitudes Survey. Self-reported days of vigorous and moderate PAs and walking were used. Ordinal logistic regression was employed to test all associations, while adjusting for age group, gender and a household asset score. Using simple mediation, testing was also done to ascertain whether obesity-related attitudes mediated associations between nutrition knowledge and PA. Results: Consistently, better nutrition knowledge was associated with disagreeing that ‘There is no reason to worry about obesity’ (ORs ≥ 1.09), but lower odds of being against ‘Providing free weight management courses’ and ‘Creating/improving cycle paths and pavements to encourage PA’ (ORs ≤ 0.90). Better nutrition knowledge was also associated with higher vigorous PA in SA (OR = 1.09), and moderate PA (OR = 1.04) and walking (OR = 1.12) in the UK. In the combined sample, associations of nutrition knowledge with vigorous PA were fully mediated by believing that ‘Obesity results from not exercising enough’ (11.1% mediated). Likewise, associations of nutrition knowledge with moderate PA were fully mediated by attitude towards ‘Creating or improving cycle paths and pavements to encourage PA’ in the UK (38.9% mediated). Conclusions: Nutrition knowledge is associated with obesity-related attitudes and PA among young adults, but some relationships are country-specific. Interventions based on findings from high-income countries should be evaluated before being implemented in low-resource settings.